Implikasi Restorative Justice dalam Tindak Pidana Pencurian terhadap Over Kapasitas Lembaga Pemasyarakatan - Dwi Lulu Afsan Saputra; Yusuf Saefudin; Selamat Widodo; Indriati Amarini (Universitas Medan Area, 2026)
Criminal justice practices in Indonesia are still dominated by imprisonment, including in theft cases, which contributes to the overcapacity of correctional institutions and is not fully oriented towards redressing victims' losses. This study aims to analyze the application of restorative justice in theft cases based on the Indonesian criminal law framework, examine its relevance from a progressive legal perspective, and examine its implications for efforts to reduce correctional overcapacity. The study uses a normative legal method with a statutory approach and a conceptual approach through literature review. The results show that restorative justice has normative legitimacy in the Indonesian criminal law system through the new Criminal Code and various implementing regulations that emphasize redressing victims' losses, perpetrator responsibility, and peaceful conflict resolution. The application of restorative justice is also in line with progressive legal theory because it positions law as an instrument for realizing substantive justice and social benefits. The novelty of this study lies in the analysis of the relationship between restorative justice in theft cases, a progressive legal perspective, and its contribution to overcoming correctional overcapacity as part of the reform of the criminal system in Indonesia.